THE ROLE OF SOCIAL MEDIA IN LEARNING ENGLISH - Xabibullayeva Gulsanam, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Introduction: In today’s digital age, social media has become an integral part of our daily lives. Platforms like YouTube, Instagram, TikTok, and Facebook are not only tools for communication but also powerful resources for learning. Among these, learning English through social media has gained immense popularity due to its accessibility, flexibility, and engaging content. This thesis explores how social media platforms can be effectively utilized to enhance English language skills, focusing on vocabulary, grammar, pronunciation, and communication abilities.Significance of the Topic: Learning a language requires consistent practice and exposure to authentic materials. Traditional methods such as textbooks and classroom lessons are often limited in providing real-life contexts. In contrast, social media offers dynamic and interactive ways to immerse learners in the English language. For instance, watching short videos on TikTok or following English-speaking influencers on Instagram allows learners to observe natural speech patterns and cultural nuances. This thesis aims to highlight the advantages of using social media for English language acquisition and provide practical recommendations for learners and educators.